2020
DOI: 10.4314/rjeste.v3i1.12
|View full text |Cite
|
Sign up to set email alerts
|

Sulfate attack and embedded steel corrosion resistances of volcanic-aggregate concrete with fly ash and silica fume

Abstract: Construction materials are increasingly on high demand in the developing world. The construction industry has a challenge of discovering, new  alternative construction materials to conventional materials which are locally available materials in environmentally friendly manner. The  experimental tests are conducted on volcanic concrete system to analyze its properties especially corrosion resistance potential for its applicability in construction. The major aim is to investigate its suitability and corrosion re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The test results indicated that SAC failed prematurely after the peak point under the similar strength condition, owing to the brittleness of the SCA. Furthermore, volcanic scoria aggregate could also improve the durability (e.g., corrosion resistance) of concrete based on the corrosion potential and linear polarization resistance tests [13,14], and the shock absorption performance of lightweight concrete adopting SCA was higher compared to OC through the impact test [14]. However, the ductility and deformability of concrete adopting SCA were inferior to those of OC due to the lightweight aggregates.…”
Section: Introductionmentioning
confidence: 99%
“…The test results indicated that SAC failed prematurely after the peak point under the similar strength condition, owing to the brittleness of the SCA. Furthermore, volcanic scoria aggregate could also improve the durability (e.g., corrosion resistance) of concrete based on the corrosion potential and linear polarization resistance tests [13,14], and the shock absorption performance of lightweight concrete adopting SCA was higher compared to OC through the impact test [14]. However, the ductility and deformability of concrete adopting SCA were inferior to those of OC due to the lightweight aggregates.…”
Section: Introductionmentioning
confidence: 99%